AMPK/mTOR pathway significance in healthy liver and non‐alcoholic fatty liver disease and its progression - Marcondes‐de‐Castro, Ilitch Aquino; Reis‐Barbosa, Pedro Henrique; Marinho, Thatiany Souza; Aguila, Marcia Barbosa; Mandarim‐de‐Lacerda, Carlos Alberto (Journal of gastroenterology and hepatology, 2023)
Obesity is related to several organs, but the liver is particularly affected. Adenosine monophosphate‐activated protein kinase (AMPK) is a cellular energy sensor and regulator of liver lipid dysfunction and glucose metabolism. The mechanistic target of rapamycin (mTOR) is a protein kinase regulating cell growth, survival, metabolism, and immunity. Together, these pathways are involved in obesity, insulin resistance, non‐alcoholic fatty liver disease (NAFLD) and its progression, and autophagy. During energy demand, liver kinase B (LKB) phosphorylation helps activate the AMPK/mTOR pathways. Likewise, the protein forkhead box O family (FOXO) negatively regulates adipogenesis by binding to the promoter sites of peroxisome proliferator‐activated receptor‐gamma coactivator 1‐alpha, initiating adipogenesis. In addition, acetyl‐CoA carboxylase, which regulates de novo lipogenesis, is linked to LKB and FOXO in developing NAFLD. The kinase complex, consisting of Unc‐51‐like autophagy‐activating kinase 1 or 2 (ULK1, ULK2) by stimulating autophagy, and eliminating fat droplets in NAFLD, is regulated by mTORC1 and negatively regulated by AMPK that suppresses liver lipogenesis and increases fatty acid oxidation. Also, ULK1 is essential for initiating phagophore formation, establishing macrophagy, and generating autophagosomes. The selective breakdown of lipid droplets through macroautophagy, or macrolipophagy, occurs on a cellular energy level using free fatty acids. In addition, mTORC1 promotes lipogenesis by activating sterol regulatory element‐binding protein. Finding new components and novel regulatory modes in signaling is significant for a better understanding of the AMPK/mTOR pathways, potentially facilitating the development of future diagnostic and therapeutic strategies for NAFLD and its progression to non‐alcoholic steatohepatitis, cirrhosis, and hepatocellular carcinoma. AMPK activation appears in a healthy liver during fasting in response to energy generation needs. AMPK enhances FA oxidation and autophagy, reducing lipid accumulation. mTORC1 activation occurs in high food intake in a diseased liver, leading to lipogenesis, reducing FA oxidation, lipolysis, and autophagy, leading to liver lipid accumulation and NAFLD. ACC2, acetyl‐Coa carboxylase 2; AKT, protein kinase B; AMPK, AMP‐activated protein kinase; CPT1, carnitine palmitoyl transferase I; DNL, de novo lipogenesis; FA, fatty acid; GTP, GTPase‐activating protein; HSL, hormone‐sensitive lipase; IR, insulin receptor; LKB, liver kinase B; mTOR, mechanistic target of rapamycin; NAFLD, non‐alcoholic fatty liver disease; PGC‐1α, peroxisome proliferator‐activated receptor‐gamma coactivator‐1 alpha; PI3K, phosphoinositide 3‐ kinase; PPARa, peroxisome proliferator‐activated receptors alpha; RHEB, Ras homolog enriched in the brain; TSC, tuberous sclerosis complex; ULK1, unc‐51‐like kinase 1.